The Study of health literacy in pregnant women with nausea and vomiting - Zahra Kamali; Zahra Abedian; Ala Sabermohamad; Reza mazlom (Mashhad University of Medical Sciences, 2017)
Background and objective: The health literacy includes person's capacity to learn and interpret information. Nausea and vomiting in pregnancy is the most common medical condition in pregnancy first three months that can be stressful for pregnant women and the family. The important role of health literacy in understands the risks before birth by mothers. The objective of this study was determining the health literacy of women with nausea and vomiting in pregnancy. Methods: In a cross-sectional study, 100pregnant women who referred to treatment centers in Neishabur County in year 2015 were investigated using the short test of functional health literacy and modified-PUQE. After confirming the validity and reliability were used. Data were analyzed using SPSS software. Results: According to the findings, the age average of participants was25.80%, 81.7%of samples were housewife,21.7%below high school diploma,and47%had average income.45.8 %of subjects had inadequate literacy level,35.6%border health literacy and18.6%had enough health literacy. Health literacy had significant association with Chi-Square Tests with, mother’s education level and age (p<0.05). Pearson is showed also a significant association between health literacy and severity of nausea and vomiting (P<0.001).This study also indicated that thereafter the health staff (71.7%) were the most important reference for obtaining health information for the responders. Conclusion: The present study indicated that the limited health literacy. The may affect mothers' perception of risk and their desire to follow the recommendations pregnancy. So should considered health literacy especially in pregnant women with lower levels of education and severe nausea.   Paper Type: Research Article.